Design, construction and operation of a solar powered ammonia–water absorption refrigeration system in Saudi Arabia. (February 2016) - Said, S.A.M.; Spindler, K.; El-Shaarawi, M.A.; Siddiqui, M.U.; Schmid, F.; Bierling, B.; Khan, M.M.A.
Highlights: Experimental investigation of a solar powered NH3 –H2 O absorption refrigerator. Results indicated COP of 0.69 at GEN/COND/EVAP temperatures of 114/23/−2 (°C). Results indicated COP of 0.42 at GEN/COND/EVAP temperatures of 145/45/−4 (°C). Abstract: This study presents an experimental investigation of a solar thermal powered ammonia–water absorption refrigeration system. The focus of this study lies on the design of the components of the absorption chiller, the ice storages and the solar collector field as well as the integration of the data acquisition and control unit. An ammonia–water (NH3 /H2 O) absorption chiller was developed in the laboratory of the Institute of Thermodynamics & Thermal Engineering (ITW) at the University of Stuttgart (Germany). A demonstration plant was built in the laboratory of the CoRE-RE at King Fahd University of Petroleum & Minerals (KFUPM – Saudi Arabia). The whole system was tested successfully. The results of the experiments indicated a chiller coefficient of performance (COP) of 0.69 and a cooling capacity of 10.1 kW at 114/23/−2 (°C) representing the temperatures of the generator inlet, the condenser/absorber inlet and the evaporator outlet respectively. Even at 140/45/−4 (°C), the chiller was running with a cooling capacity of 4.5 kW and a COP of 0.42.